Telaah Metodologi Istinbath Dan Corak Hukum Islam Pada Lembaga–Lembaga Fatwa Di Indonesia - Yuhanna putri wahyuningrum (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
This study examines the istinbath methodology and the characteristics of Islamic law implemented by fatwa institutions in Indonesia, specifically the Lajnah Bahtsul Masail Nahdlatul Ulama (LBMNU), Majelis Tarjih Muhammadiyah, and the Fatwa Commission of the Indonesian Ulama Council (MUI). Islamic law, as a vital aspect of Muslim life, continues to adapt and evolve in response to socio-cultural and political dynamics. Its legal products are not confined to fiqh books but also encompass scholars' fatwas, decisions of religious courts, and legislative regulations. The research focuses on how these institutions utilize the istinbath methodology to address contemporary issues, including social transformations, technological advancements, and new challenges absent from classical jurisprudence. By employing library research and descriptive-analytical methods, this study highlights that issuing fatwas requires more than just relying on the textual sources of the Qur'an and Hadith or classical scholarly opinions. Instead, a more dynamic and context-sensitive ijtihad approach is essential for resolving modern problems effectively.